Role of A Body Shape Index (ABSI) in Clinical and Public Health Practices: A Correlational Study on Igbo Adults, Southeast Nigeria - Obaje, Sunday; Sonia‑Love, Okorie; Egwu, Oguguo (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context: The role of A Body Shape Index (ABSI) has gained attention in both clinical and public health realms due to its potential in predicting health outcomes. This study focuses on Igbo adults in Southeast Nigeria, a population with limited ABSI-related research. Aim: It focuses solely on the relationship between ABSI and blood pressure for a healthy living in Nigeria. Research Settings and Design: The study enrolled 200 Igbo adults aged 18–25 years. Measurements including height, weight, waist circumference, and blood pressure were collected using measuring tapes, weighing scales, and blood pressure monitors. Statistical analysis employed SPSS version 20, with a significance level of P< 0.05. Results: The mean ABSI remained consistent across various age groups and genders. An explicit positive correlation between age and ABSI was observed. Despite a low area under the curve (AUC) of 0.450 in receiver operating characteristic (ROC) analysis, ABSI exhibited optimal predictive capability with a specificity of 77.00% and sensitivity of 35.7%. Conclusion: ABSI emerges as a newer and promising alternative index for blood pressure predictions. Its incorporation in clinical and public health practices can enhance disease predictability. This study provides critical insights into the applicability of ABSI within the Igbo population and underscores its potential utility in broader healthcare contexts.